Uma Estratégia para Institucionalização de Iniciativas para Interdisciplinaridade de IHC aplicada ao Ensino de Programação - P. Britto, Nathalino; Elizabeth S. Furtado, Maria; P. L. Cardoso, Rafaela (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2018)
IHC's interdisciplinarity teaching solutions generally focus on supporting teachers to plan classes and organise didactic content. Given this context, some studies show that in the algorithms ' disciplines of a computational course there is a logical complexity that requires more attention. In this perspective, we perceive the need to support those involved to implant the interdisciplinarity of IHC in a course that had algorithm discipline. Thus, this article defines and describes a strategy that describes the key elements and activities for such deployment and evaluation. To do so, a case study was carried out to analyze the difficulties in a course for the students of the algorithm discipline to analyze and correct an example with usability error, verified through a heuristic inspection.